Response Of Islamic Educational Institutions TowardsThe Era of Society 5.0 - Susilo Surahman; Mudofir Mudofir; Baidi Baidi (At-Tarbiyat, 2021)
Society 5.0 is in line with the industrial revolution 4.0 where both bring technology as a new world change. This research aims to understand the basic concepts of society 5.0 and Islamic educational institutions' readiness to address them. This research uses a descriptive qualitative approach. Data sources are obtained through literature studies and analyzed using descriptive analysis. The results show that the basic concept of society 5.0 is directed at human comfort in all joints of life or activity through technology optimization. Islamic educational institutions are required to cultivate values to stem the negative influence of changes and the development of the times, both society 5.0 in line and the industrial revolution 4.0.